JURIDICAL ANALYSIS OF LEGAL CONSIDERATIONS FROM THE JUDGE IN CANCELING THE DETERMINATION OF THE HEIRS NUMBERS 89/PDT.P/2020/PA.BN AT THE CLASS IA BENGKULU RELIGIOUS COURT - Septilia, Eka; Ma’akir, Hamdani; Akhmad (Bengkoelen Justice : Jurnal Ilmu Hukum, 2025)
The purpose of this research is to examine and analyze the legal considerations of the Panel of the Judges in Canceling the Determination of Heirs Number 648/Pdt.G/2022/PA.BN towards the Cancellation of the Determination of Heirs Number 89/Pdt.P/2020/Pa.Bn at the Class IA Bengkulu Religious Court. The method used in this research is normative method by analyzing existing decisions and statutory regulations. The results of the research show that the legal considerations of the Panel of the Judges in Canceling the Determination of Heirs Number 648/Pdt.G/2022/PA.BN towards the Cancellation of the Determination of Heirs Number 89/Pdt.P/2020/Pa.Bn at the Class IA Bengkulu Religious Court was done based on the Islamic and Positive Law in Indonesia, by looking at written evidence and witnesses at the trial, and has fulfilled the elements of legal certainty and justice for all parties. Keywords: Legal Considerations, Cancellation of the Determination of Heirs, Religious Court